Pengembangan multimedia interaktif berbantuan canva untuk menumbuhkan berpikir kritis siswa dalam pembelajaran ilmu pengetahuan sosial - Suryani, Sri; Zainudin, Mohammad; Anggraini, Ade Eka (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2024)
Learning using interactive learning multimedia is more effective and easy to understand by students so it can be used to increase students' motivation and thinking skills. Therefore, this study aims to produce media in the form of interactive learning multimedia that is valid, practical, and effective in improving students' critical thinking skills.  This type of research is an R&D research using Analysis, Design, Development, Implementation, and Evaluation. The subjects of the small group test in this study were 10 students while the subjects of the large group test were 24 students. The object of this study is the quality of media in the form of interactive learning multimedia for social studies learning as seen from the results of validity, practicality, and effectiveness of media. The data collection instruments used in this study are using qualitative and quantitative approaches that include interviews, questionnaires, and tests. The results of the study showed that 1) the results of the validation of media experts obtained very valid and material experts obtained very valid; 2) the results of the student response questionnaire obtained very practical and the results of the teacher response questionnaire obtained very practical; 3) The effectiveness of the media can be seen in the results of the t-test calculation where the sig value is 0.00 < 0.05, which means that H0 is rejected and H1 is accepted. From the results of these acquisitions, it can be concluded that there is a significant difference after using interactive learning multimedia. Based on the results of the study, it can be concluded that interactive learning multimedia using Canva is declared valid, practical, and effective to improve students' critical thinking skills.